Religião e política: a participação política dos pentecostais nas eleições de 2002 - Bandini, Claudirene Aparecida de Paula (2003)
From the decade of 80 the religions had come back to the public sphere and if they had presented apt to represent important public papers in the continuous construction of the modern world. In the context of the globalization, the religious identities had in accordance with suffered to a re-significação from its originary contents the social process and the local lexicon. Of this form, the pentecostalismo if constitutes how much it saw alternative to the excluded individuals either finding an access to modernity either to the rescue of auto-esteem. The electoral process in allows them to verify the "desprivatização " of the pentecostais groups when producing new signs by means of the border politics and symbolic in which they fulfill the paper of expression of the group. Its articuladores if appropriate of religious goods and they associate them with the system of prestige and power. After that, they develop a new way to see the connection politics and religion, therefore they start to negotiate a new space front to the other social groups. The analyzed process if relates to the contextualização of the politics-religious career of pentecostais candidates e, respectively, the electoral strategies of the churches Assembly of Deus, Church of Evangelho Quadrangular and Universal Church of the Kingdom of Deus.